Effects of post-workout supplements and resistance training on serum metabolome, muscle strength and muscle hypertrophy - Tommola, Salli (2017)
Human metabolism is a complex mixture of different metabolites and metabolic pathways that are interrelated. Compared to standard biomarker assessments, metabolomics gives a broader perspective of the whole ensemble thus deepening the understanding of human physiology and pathophysiology. The aim of this study was to provide a comprehensive overview of the effects of different post-exercise supplementation regimens and different resistance training programs on serum metabolome and resistance training adaptations. 60 healthy men volunteers (mean ± SD: age 32.6±6.7 y; height 1.80±0.1 m; weight 82.8±10.4 kg and BMI 25.5±3.0 kg/m2) were included in the study. All the participants went through a resistance training program, including a 4-week familiarization phase and the actual 12-week intervention phase. Before the intervention phase, the subjects were randomly split into protein (PROT), carbohydrate (CHO) or protein+carbohydrate (PROT+CHO) groups and further into hypertrophic (HYP) or maximal+power (MAX+POW) resistance training groups. Fasting blood samples were collected and metabolites were analyzed by an automated high-throughput serum nuclear magnetic resonance (NMR) spectroscopy, body composition was assessed by dual-energy X-ray absorptiometry (DXA), cross-sectional area (CSA) of vastus lateralis was assessed by ultrasound and maximal isometric strength was measured in leg extension dynamometer before and after the 12-week intervention phase. The serum metabolome profiles did not differ significantly after the different training and supplement regimens in between group comparisons. Thereafter, the study groups were combined to examine the changes in dyslipidemia biomarkers. Although there were no significant changes, the tendency was towards more beneficial metabolite profile: LDL cholesterol (mean ± SE: -1.1 ±2.8 %), HDL cholesterol (+4.2 ±1.9 %), serum cholesterol (-0.4 ±1.6 %), triglycerides (-1.7 ±3.4 %). Conversely, in blood glucose the change was adverse (+0.9 ±1.3 %). Muscle strength (p=0.001) and size increased (p=0.003) in all study groups. MAX+POW group increased more CSA of vastus lateralis (9.5 ±16.9 % vs. 6.9 ±16.8, % p=0.04) than HYP group. Although the finding was not statistically significant, HYP group had a greater increase in maximal isometric strength (13.8 ±42.9 %, p=0.001) compared to MAX+POW group (6.7 ±44.8 %, p=0.008). Of the supplement regimens, PROT group (p=0.001) and of the training programs, HYP group (p=0.001) had the most pronounced effects on all the variables of body composition shifting the values towards leaner body composition. The main finding of this study was that the present resistance training intervention resulted in healthier metabolite profiles among the whole group of participants. Especially, dyslipidemia biomarkers shifted towards better values reducing the risk of having metabolic diseases. Moreover, enhancements were produced also in body composition and maximal muscle strength. The importance of resistance training should be highlighted as it appears to have broad beneficial influence in metabolism and body composition in previously untrained men thus resulting in a better health state.